Green paper on relations between the European Union and the ACP countries on the eve of the 21st century : challenges and options for a new partnership (European Commission BrusselsBE, 1996)
Assesses what has been achieved and looks at major political, economic and social trends. Outlines ideas and options for breathing fresh life into the ACP-EU partnership and recharging it with the relevance and effectiveness needed to face up to the challenges of the 21st century.
Additional copy located in Office of the Secretary-General